Ureditev zastaranja odškodninskih terjatev zaradi kršitev konkurenčnega prava v Direktivi 2014/104/EU in njena implementacija v pravne rede držav članic - Vlahek, Ana (Pravnik, 2017)
The article analyses provisions on limitation of antitrust damages actions set out in Directive 2014/104/EU on certain rules governing actions for damages under national law for infringements of the competition law provisions of the Member States and of the European Union in the light of modern trends in the law of limitation. It presents the Member States' (draft) implementing legislation from the perspective of their national general rules on limitation. Within that, a particular focus is placed upon the analysis of the limitation regime introduced in the latest draft amendment to the Slovenian Prevention of Restriction of Competition Act that includes provisions transposing the directive into the Slovenian legal system. A critical assessment of the relationship between the draft legislation and the general Slovenian regime of limitation of actions in tort set out in the Obligations Code is also provided.
Keywords: konkurenčno pravo; odškodninske terjatve; odškodninski zahtevki; preprečevanje omejevanja konkurence; zastaranje